The Effectiveness of Strategic Planning in Improving the Performance of Industrial Enterprises: A Case Study on Ammouri Complex - Biskra, Algeria - Benkhalifa , Ahmed; Amouri , Fadia; Labbaci , Ramzi (The Arab Journal of Administration, 2019)
This study aimed to identify the trends at the Amouri Group of Biskra workers towards the level of the prevailing strategic planning and also identify the prevailing level of the prevailing institutional performance at Amouri Group, this adds to the knowledge of the impact of strategic planning with its various dimensions on the performance at Amouri Group, The target population of the study consists of administrative workers at the Amouri Group of Biskra totaling (351) workers, The student used simple random sample method and a volume of (160) workers, Where the questionnaire was distributed them through several field visits, And recovered of which (110) questionnaire is valid for statistical analysis. The student has used the descriptive analytical approach to reach the results of the study Has been relying on several statistical methods to analyze data, including: Scale descriptive statistics, regression analysis, analysis of variance, and test T-TEST, This study concluded that several of the most important results: That the level of prevailing strategic planning at Amouri Group of Biskra came medium, and the level of performance at Amouri Group com high, the results shows as well the existence of a statistical effect of the independent variables: (Configuration and Step, The Development of strategic plan, The Implementation of strategic plan), also the absence of any impact in the Analyses of the current situation at Amouri Group, Where the strategic planning explained (49.2%) of the changes taking place in the level of Amouri Group performance, based on the value of the coefficient of determination R2, The study found many of the recommendations include: The Group have to determine its performance indications and measures then from time to time to determine the degree of the actual Group performance, and compared with to performance achieved in previous periods and company then as well with other similar institution. Also, they should work on the development of management information systems and constantly updated to contribute for providing the basic information to practice strategic planning process with an appropriate quality at the right time. And apply all the programs that help making decision, The existence of a direct relationship between knowledge management as an independent variable (generation, dissemination, application) and the dependent variable of competitive advantage through its dimensions, and the study showed that there is a significant weakness between the application of knowledge management and competitive advantage in the company will be accurate.,